What can biomechanics reveal about rowing? - Smith, R. M.; Loschner, C. (2008)
Success in competitive rowing is achieved by taking the shortest time to complete a 2000 m course. This time is mathematically linked to the average velocity of the boat. Thus factors that affect boat velocity are important determinants of rowing performance. The above biomechanical analysis of rowing reveals a number of key variables that determine the velocity of the boat. Following the breakdown of variables in this figure leads to the forces that affect boat velocity: propulsive pin (rowlock) forces, propulsive stretcher (foot plate) forces, and water and air resistance, the sum of these being the net boat force. Water resistance will also be affected by transverse and vertical pin, stretcher and seat forces as these affect the attitude of the boat and thus the cross-sectional area and skin surface area presented by the boat to the water and wave creation. Factors that rowers can manipulate are the magnitude and timing of forces on the oar handle(s), seat and stretcher and the coordination of the joint angles of the rower's body. The oar handle force, in turn affects the pin force via the lever and hydrodynamic system of the oar. Overall performance then depends on the rower's fitness and ability to optimise the application of forces.